The elephant and its economic and recreational importance in the city of Sabratha during the Roman era (146 BC - 211 AD) (Faculty of Education Scientific Journal, 2024)
This topic is concerned with researching the economic and recreational importance of the elephant in the ancient city of Sabratha, as it is one of the important topics in ancient history, in addition to the abundance of archaeological sources such as rock drawings, murals, and minor arts that depict elephants in ancient Sahara Desert civilizations.     This topic highlights the role played by the African elephant in terms of the economic importance of elephants in ancient Africa in general and Sabratha in particular, as they are concentrated in the ivory trade and its industrial and artistic uses. Ivory was one of the most important trade materials in ancient Africa between North and South, in addition to foreign trade, and its trade brought many benefits to its owners.    The main goal of the study is to highlight the role of the elephant and its multiple uses in the Libyan city of Sabratha. It is known that elephants were domesticated in advanced periods of ancient Libyan history, especially in the Sahara Desert, to benefit from their physical strength. They were used during celebrations and recreational games, in addition to using their tusks and skins. For commercial purposes. It is not surprising that the elephant appears on currency engravings due to its economic importance.   The importance of the study is due to the fact that it deals with a living creature that is photographed, which is the elephant, which is distinguished by its strength and its economic and entertainment importance, by reviewing a number of images and currency topics to explain their uses and why they are uniquely important in the fields of economics and entertainment.Here it must be noted that previous studies of the role of the elephant did not focus on the importance of the elephant in the city of Sabratha in particular. Here there was an urgent need for a study on the elephant and its economic importance in transportation and trade, as well as its recreational role.
Keywords: elephant; Rock art; Ivory